2022
DOI: 10.21203/rs.3.rs-2014117/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The lncRNA Snhg11 is required for synaptic function, neurogenesis and memory and is downregulated in the dentate gyrus of Down syndrome mouse models

Abstract: Down syndrome (DS) is the most common genetic cause of intellectual disability. Even though advances in the last decades have allowed better delineation of its pathogenetic mechanisms, its cellular and molecular bases are still poorly understood. Here, single-nuclei transcriptional profiles of the hippocampus of a DS mouse model revealed that the trisomy results in a highly cell-type specific alteration of the transcriptome. Strikingly, we observe a major transcriptomic shift in trisomic granule cells from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 98 publications
(132 reference statements)
1
2
0
Order By: Relevance
“…A sparser neuronal ensemble activation was also detected in a previous study in the CA1 region of Ts65Dn, upon exposure to novel environments [24]. In addition, a recent study from our laboratory found a lack of upregulation of Arc levels immediately after learning in Ts65Dn mice while Arc levels did not differ in basal conditions [25]. It might be possible that cell-autonomous mechanisms, such as impaired intrinsic excitability [39,40,45] or non-autonomous factors might lower the number of active neurons in response to learning cues.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…A sparser neuronal ensemble activation was also detected in a previous study in the CA1 region of Ts65Dn, upon exposure to novel environments [24]. In addition, a recent study from our laboratory found a lack of upregulation of Arc levels immediately after learning in Ts65Dn mice while Arc levels did not differ in basal conditions [25]. It might be possible that cell-autonomous mechanisms, such as impaired intrinsic excitability [39,40,45] or non-autonomous factors might lower the number of active neurons in response to learning cues.…”
Section: Discussionsupporting
confidence: 79%
“…Cognitive deficits have been extensively described in Ts65Dn mice, especially deficits in hippocampal-dependent tasks such as NORT [25,32] and CFC [15,33]. During the training session, Ts65Dn mice showed normal performance along the training session, with a significant increase of freezing during the training session to levels similar to the WT (ANOVA repeated measures; F(3,18) = 0.88; genotype effect N.S.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation